Yuppie’s parental decisions on children vaccination in the east coast region, malaysia - Noor Amira Syazwani, Abd Rahman (2024)
Vaccination plays a central role in public health through the early prevention and controlling of infectious diseases, especially among children. Although vaccination is widely recognised as one of the most effective preventive measures in public health, a growing number of parents consider it unnecessary. In addition, the increasing instances of vaccination refusal poses a challenge to achieving optimal vaccination rates. This study examines the factors that influence the vaccination intentions and behaviours of young urban professional (Yuppies) parents in East Coast Region, Malaysia. A purposive sampling method was employed, yielding a total of 357 respondents for the study. The hypotheses were tested using Structural Equation Modeling (SEM) with Smart PLS version 4.0. This study examines the relationships between a few identified factors - such as perceived susceptibility, severity, barriers, attitudes, subjective norms, and perceived behavioural control — and their effect on parents' vaccination intentions and behaviours. It also examines how perceived policy effectiveness (PPE) and social media influence moderates these relationships. Results show that perceived susceptibility, perceived barriers, attitudes, subjective norms, and perceived behavioural control significantly influences vaccination intentions. Perceived severity, on the other hand, has little influence on vaccination intentions, indicating the need for tailored communication about the importance of disease severity. Furthermore, perceived policy effectiveness does not significantly affect the relationship between the variables and vaccination intentions of parents. However, when perceived policy effectiveness matches subjective norms, vaccination intentions are noticeably strengthened. Surprisingly, the influence of the media does not significantly strengthen the relationship between intentions and actual vaccination behaviour. Exposure to vaccine-relevant media content does not consistently lead to increased vaccination behaviour. This analysis of the determinants, perceived policy effectiveness and social media influence sheds light on the vaccination decisions of Yuppie parents in Malaysia. Tailored communication, better accessibility of vaccination, and stronger policies are crucial to overcome vaccination hesitancy and increase vaccination rates. This study also contributes to the understanding of parental decisions towards vaccination of children in Malaysia. It not only provides a foundation for future studies that examine parental intentions and behaviours related to vaccination but also provides valuable insights for policymakers and government agencies, which includes the Public Health Department, the Ministry of Health, and other health-related agencies. By identifying factors that influence vaccination rates, this study can assist in the intervention developments aimed at increasing vaccination coverage and boosting population immunity